Conflitos de tarefas e conflitos afetivos: Relações com a percepção de planejamento estratégico em cooperativas médicas - Ezequiel, Cristiane Fernandes (2023)
The objective of this research was to analyze task conflicts and affective conflicts and their relationships with the perception of strategic planning in medical work cooperatives spread across Brazil. There is an extensive literature that demonstrates the complex dynamics related to conflict, in which individual, contextual and organizational characteristics can increase or reduce conflict levels in a team. There are also differences between the types of task and affective conflicts, which determine whether they will be harmful or, in some situations, beneficial, influencing the focus on strategic decisions. The context of health cooperative management presents itself as a favorable environment to better understand this phenomenon. In this scenario, strategic planning is developed in a more robust way, considering all stakeholders involved, such as cooperating doctors, employees, customers, competitors, suppliers and other stakeholders. The proposed research adopted a quantitative approach, using a measurement scale based on the typology of task and affective conflicts. It was carried out based on data collected from senior management, with doctors who are members of boards, superintendents, managers and coordinators. The divergence can begin with a debate of different points of view and, characterizing the conflict of tasks, and without consensus, evolve into an affective conflict, impacting the human relationships existing in the cooperative. However, the research concluded that conflicts at this stage do not influence the preparation and implementation of strategic planning. Therefore, the importance of effective emotional management is highlighted, aiming to develop organizational maturity that allows for argumentative divergences with the aim of improving decision-making, without affecting the personal and emotional aspects of those involved, focusing on the process and execution of the task. in favor of the best solutions, not becoming personal confrontations.